BUSINESS DEVELOPMENT IN UKRAINE: CURRENT STATE, CHALLENGES, AND PROSPECTS - HRYSHYNA, Nataliya; HOROVY, Oleksiy (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The significance of studying business development in Ukraine lies in its strategic importance for economic growth, social stability, and national recovery during wartime and the post-war reconstruction period. The key aspects that determine the relevance of this research area include: the restoration of national and regional economies, the creation of a favorable investment climate, adaptation to the challenges of war, digitalization and innovation, social responsibility, and resilience.The purpose of this article is to analyze the current state, challenges, and prospects of business development in Ukraine under the conditions of war.Results. An analysis of the current state of business development has shown that the majority of active business entities are sole proprietors (individual entrepreneurs), accounting for 83.9% of the total in 2023. This form of business is the simplest, most convenient, and least costly way to operate a small enterprise. Overall, over the past twenty years, the number of active business entities has decreased by 1.14 times or by 270,848 units. It has been proven that the agricultural sector remains not only a traditionally strong industry for Ukraine but also one of the key drivers of economic recovery and growth. It is emphasized that sectors aligned with global trends (technology, energy efficiency, security) or those addressing basic domestic needs (food, healthcare, education, logistics) remain attractive for business in Ukraine. The most promising areas are those that combine local resources, innovation, and export potential.Conclusions. The main challenges hindering business development in Ukraine have been identified. It is noted that these problems are multifaceted, involving both external and internal factors. Currently, they are largely driven by military actions, economic instability, legislative imperfections, and other critical issues. It has been demonstrated that business development in Ukraine faces numerous challenges requiring a comprehensive approach to resolution. It is emphasized that it is not only important to adapt businesses to new realities but also to create a stable, transparent, and predictable environment for entrepreneurial activity. Both the state and international partners must play a key role in this process.
Keywords: business; challenges; prospects; martial law; development and recovery of regions; attractive economic sectors; national and regional economy